Transmisi Budaya Islami pada Lembaga Formal: Studi Kasus di SDIT Al Izzah Kota Sorong Papua Barat, Indonesia - Indria Nur (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2022)
This study aims to describe and analyze the transmission of Islamic culture in educational institutions through organizational culture theory. The data was obtained from key informants through interviews, observation and documentation. Some theories were used in this study, including Schein's tripartite theory which is integrated with Berry's transmission theory, and the cultural theory of Koentjaraningrat. The research results show that the al Izzah Integrated Islamic Elementary School is very concerned about the process of transmission that takes place within the institution. This is evident from the agreement on Islamic cultural values that are enforced in the institution through the vision and mission, the culture of values that go well and appropriately, after going through a continuous socialization process from both educators, school principals, parents and stakeholders within the scope of the institution. In addition, there is also support and awareness of the role of the transmitter as a good example, the collaboration of all parties, in this case the principal, educators, parents and the community, in creating a sustainable Islamic culture that shows the internalization of Islamic values in the daily life of the students at SDIT al Izzah both in the school and home environment.